Strength of Evidence of Electronic Media (Teleconference) In The Criminal Justice System - Mamulai, Muslim; Djanggih, Hardianto; Wahab, Mirnawanti (VRIJSPRAAK : International Journal of Law, 2017)
The strength of the evidence of Electronic Media (teleconference) in the process of proving a criminal case according to the Criminal, specify a limited manner valid evidence and procedures for the use of that evidence thus have legal power of proof. Proof via electronic media (teleconference) regulates the judge / magistrate constitutional obligation to seek and find the truth so that the material taken into consideration for the judges in deciding a case. Implementation of evidence through electronic media in a criminal act, should the judge may use the priority when it will use the values ââof the basic purpose of the law (justice, expediency and certainty) to accommodate the evidence through electronic media in examining the crime of existing.